Spatial Assessment of Public Water Supplies in Densely Populated Areas of Ilorin Metropolis, Kwara State, Nigeria (Fountain Journal of Natural and Applied Sciences, 2014)
Water samples collected from public tap supplies at densely populated areas within Ilorin metropolis were analyzed for potability and safety. The study covered a period of twenty-four months. Physicochemical parameters such as pH, turbidity, residual chlorine, colour, suspended solids and total hardness were determined. The pH of the samples ranged from 7.0 - 7.90 while the range for residual chlorine was 0.5 - 10 mg/L. The suspended solids and total hardness ranged from 0.79 - 46.0 mg/L and 7.0 - 34mg/L respectively. Turbidity of the samples ranged from 0 – 5 NTU, while the colour range was 0 - 5 HU and temperature range was 21 - 30 0C. The results show that only four (20%) of the twenty samples were potable and free from pathogens while Escherichia coli, Klebsiella sp., Salmonella sp., Pseudomonas aeruginosa, Shigellla sp. and Enterobacter aerogenes were detected in sixteen (80%) of the samples. The viable total bacterial count ranged between 0.00 – 2.6 x 102 cfu/mL, total coliform count ranged from 0 – 75 MPN/100mL while faecal coliform count ranged from 0.00 – 2.3 x 102 cfu/mL. The presence of coliforms in the samples is indicative of faecal and non-faecal contamination along the supply network, which in some cases could be due to leaching from contaminated environment into corroded pipes along the distribution network used for conveying the treated water that passed through drainage system.Keywords: Coliforms, contamination, safety, bacteriological, physicochemical parameters